PENGUKURAN KEPUASAN MASYARAKAT ATAS PELAYANAN PUBLIK DI KECAMATAN CEMPAKA KOTA BANJARBARU - Eka Yulita Dewi (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
Abstract: This study aims to find out to find out the measurement of community satisfaction with public services in the Cempaka Subdistrict, Banjarbaru City based on the Community Satisfaction Index (IKM) and provide input for public services in the Cempaka Sub-District of Banjarbaru City that should be done. The data analysis technique used in this study is quantitative descriptive research by taking samples of 93 respondents and using questionnaires as the main data collection tool according to KEPMENPAN Number 14 of 2017. The results of the study can be concluded based on the calculation of the Community Satisfaction Index referring to the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017, showing the performance of service units predicated